The role of the gender diversity of audit committees in modelling the quality of management earnings forecasts of initial public offers in Malaysia - Ammer, Mohammed Abdullah; Ahmad Zaluki, Nurwati Ashikkin (Emerald Group Publishing Limited, 2017)
Purpose – Presently, one of the major governance issues faced by management and shareholders of organizations is the gender composition of the boards of directors and audit committees. This study aims to examine the impact of audit committee gender on the accuracy of management earnings forecasts disclosure in IPO prospectuses. Design/methodology/approach – The study sample comprises 190 Malaysian companies issuing IPOs that transformed into public companies during the period 2002-2012. Earnings forecasts accuracy (quality) is proxied by absolute forecast error and the study model is developed based on the frameworks of the signaling theory, the agency theory and the resourcedependence theory. Findings – The study proposes that female directors introduce a set of specific features to the boardroom that serve to improve investors’ protection and efficient monitoring of management. However, according to the findings, an insignificantly positive relationship exists between audit committee gender and absolute forecast error, which shows that more female directors in the audit committee could translate into more errors and less accuracy in earnings forecasts. Practical implications – Considering the recent regulatory developments that encourage the number of women on the board of directors, the findings obtained have significant implications for policymakers. The study findings can also be invaluable to investors, investment analysts, market players and researchers. Originality/value – The composition of the board of directors and audit committee in terms of gender plays a significant role in the promotion of effective corporate governance practices. This study is one of the pioneering studies that examines the advantages of gender diversity in the board of directors. It is also the first study to extend IPO literature by investigating the role of audit committee gender in the enhancement of accurate management earnings forecasts included in the IPO prospectuses.